2022
DOI: 10.1155/2022/4838760
|View full text |Cite|
|
Sign up to set email alerts
|

EZH2 Regulates ANXA6 Expression via H3K27me3 and Is Involved in Angiotensin II-Induced Vascular Smooth Muscle Cell Senescence

Abstract: Objectives. Abdominal aortic aneurysm (AAA) has a high risk of rupture of the aorta and is one of the leading causes of death in older adults. This study is aimed at confirming the influence and mechanism of the abnormally expressed ANXA6 gene in AAA. Methods. Clinical samples were collected for proteome sequencing to screen for differentially expressed proteins. An Ang II-induced vascular smooth muscle cell (VSMC) aging model as well as an AAA animal model was used. Using RT-qPCR to detect the mRNA levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…ANXA6 overexpression has the opposite effect. EZH2 regulates ANXA6 promoter H3K27me3 modification, inhibits ANXA6 expression, attenuates Ang II-induced senescence in blood smooth muscle cells, and inhibits the progression of an abdominal aortic aneurysm (AMA) [ 107 ].…”
Section: Other Tumor-associated Phenotypesmentioning
confidence: 99%
“…ANXA6 overexpression has the opposite effect. EZH2 regulates ANXA6 promoter H3K27me3 modification, inhibits ANXA6 expression, attenuates Ang II-induced senescence in blood smooth muscle cells, and inhibits the progression of an abdominal aortic aneurysm (AMA) [ 107 ].…”
Section: Other Tumor-associated Phenotypesmentioning
confidence: 99%
“…Wang et al ( 19 ) demonstrated that EZH2 expression increases the migration of pulmonary arterial smooth muscle cells (SMCs) and participates in the pathogenesis of pulmonary arterial hypertension. EZH2 enhances apoptosis in SMCs and the formation of abdominal aortic aneurysms ( 20 ). However, the biological effects of EZH2, as well as the association between EZH2 and TAA, remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancer of zeste homolog 2 (EZH2) is a methyltransferase from the Polycomb gene family, significantly impacting VSMC proliferation and differentiation. EZH2 regulates these processes by modifying histone methylation on microRNAs and the N-terminal tail of the 27th amino acid, lysine, on core histone H3 (H3K27me3) ( Zhang et al, 2021 ; Li et al, 2022 ; Zhong et al, 2022 ). Furthermore, EZH2 influences VSMC contraction and relaxation by modulating the expression of critical genes such as those encoding calcium channels and actin.…”
Section: Introductionmentioning
confidence: 99%